Characterisation and mechanism of action of lantibiotics produced by Streptococcus salivarius / Abdelahhad Barbour - Abdelahhad, Barbour (2016)
Salivaricins are lantibiotics produced by Streptococcus salivarius, some strains of which have significant antimicrobial effects. S. salivarius strains in this study were isolated from Malaysian subjects and showed variable antimicrobial activity, metabolic profile, antibiotic susceptibility and lantibiotic production. New S. salivarius strains isolated from Malaysian subjects with potential as probiotics were investigated and reported. Safety assessment of these strains included their antibiotic susceptibility and metabolic profiles. Genome sequencing using Illumina’s MiSeq system was performed for two strains namely NU10 and YU10 and showed the absence of any known streptococcal virulence determinants indicating that these strains are safe for subsequent use as probiotics. Strain NU10 was found to harbour loci for biosynthesis of the lantibiotics specifically salivaricins A and 9 while strain YU10 harboured genes encoding salivaricins A3, G32, streptin and slnA1 lantibiotic-like protein. The full locus for biosynthesis of salivaricin G32 was sequenced and analysed for the first time in this study. The enhancement of lantibiotic production was achieved by using a newly developed medium buffered with 2-(N-morpholino)ethanesulfonic acid (MES). This showed better biomass accumulation compared with other commercial media. Furthermore, salivaricin 9 from strain NU10 and salivaricin G32 from strain YU10 were extracted and purified using S. salivarius cells grown aerobically in this medium. Additionally, salivaricins A2 and B were also recovered from strain K12 and purified to homogeneity in this study to understand the mechanism of inhibition on selected microorganisms. The binding mechanism of antimicrobial peptides was better understood using a new peptide-membrane model developed in this study using cecropin B as a model of small cationic antimicrobial peptide. This was investigated by following the fluorescence variation of tryptophan in energy and time domains. The fluorescence showed enhancement of the peak intensity of cecropin B upon mixing with the bacterial membrane accompanied by a blue shift indicating perpendicular penetration of cecropins B from its Lys side where the Trp residue of cecropin B is immersed in the bacterial membrane vesicles. Unlike cecropin B, the lantibiotic salivaricin B was not able to penetrate bacterial membrane vesicles. This was established by measuring the fluorescence of the tryptophan residue at position 17 when salivaricin B interacted with bacterial membrane vesicles. The absence of a fluorescence blue shift indicates a failure of salivaricin B to penetrate the membranes. The potential membrane permeabilization by salivaricin B was also probed in Streptococcus pyogenes and Micrococcus luteus using the molecular probe SYTOX Green. The results showed that unlike nisin A, salivaricin B did not induce pore formation in susceptible cells. Flow cytometric analysis using DiOC2(3) revealed that salivaricin B did not dissipate membrane potential in sensitive cells. On the other hand, salivaricin B interfered with cell wall biosynthesis as shown by the accumulation of the final soluble cell wall precursor UDP-MurNAc-pentapeptide which is the backbone of the bacterial peptidoglycan. Transmission electron microscopy of salivaricin B-treated cells showed a reduction in cell wall thickness together with signs of aberrant septum formation in the absence of visible changes to cytoplasmic membrane integrity.